Preparation method and application of benzothiadiazole-titanium dioxide nanosheet heterojunction composite material
By synthesizing benzothiadiazole photofunctional molecules and TiO2 nanosheets to form heterojunction composite materials, the problem of limited photocatalytic performance of TiO2 is solved and efficient photocatalytic degradation effect is achieved.
Patent Information
- Application Number
- CN202310596444.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-05-25
AI Technical Summary
The large bandwidth of TiO2 leads to a low utilization rate of sunlight and the easy recombination of electron-hole pairs, which limits its photocatalytic performance.
By synthesizing the benzothiadiazole photofunctional molecule BTDSCN and TiO2 nanosheets, hydrothermal reaction is carried out to form a benzothiadiazole-titanium dioxide nanosheet heterobond composite material.
It improves the transfer efficiency of photogenerated carriers, significantly improves the photocatalytic performance, and has excellent photocatalytic degradation performance for organic dyes and heavy metal ions.
Smart Images

Figure CN116493052B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalytic material preparation, and specifically relates to a preparation method of a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material, and also relates to the application of the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material. Background Art
[0002] Organic dye pollution and heavy metal ion pollution are two typical water pollutions. They are difficult to degrade, bioaccumulate and have biological toxicity, which have endangered people's daily life. Therefore, how to effectively and environmentally friendly remove organic dye pollution and heavy metal ion pollution is the focus of environmental protection. 2 Since the first report of photocatalytic water decomposition to produce hydrogen, TiO 2 TiO has been widely studied in photocatalysis, solar cells, lithium-ion battery electrodes, biomedical devices, and smart coatings. 2 The large band gap, low utilization of sunlight, and easy recombination of electron-hole pairs limit their photocatalytic performance and hinder their development.
[0003] In order to increase the TiO 2 The photocatalytic activity of TiO 2 Photocatalytic materials have been used reasonably, and researchers have conducted modification studies on them. The main purpose is to improve the separation efficiency of photogenerated carriers, inhibit carrier recombination, and thus improve the quantum efficiency of materials; expand the light absorption range of materials; improve the photostability of materials, etc. At present, the main ways to improve photocatalytic activity are: ion doping, surface photosensitization, noble metal particle sensitization, construction of nanomaterial heterojunctions, etc. Constructing heterojunctions is a relatively effective method and is also a method commonly used by researchers. Common heterojunctions are generally made of inorganic metal materials and TiO 2 There are very few reports on the formation of heterojunctions between organic semiconductor materials and them. Benzothiadiazole molecules, due to their large π-electron conjugated system, often have excellent photoelectric capabilities and are the most ideal molecular type for organic semiconductors. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material, thereby improving the transfer efficiency of photogenerated carriers and further improving the photocatalytic performance thereof.
[0005] The technical solution adopted by the present invention is a method for preparing a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material, which is specifically implemented according to the following steps:
[0006] Step 1, synthesizing benzothiadiazole photofunctional molecule BTDSCN;
[0007] Step 2: Combine the benzothiadiazole photofunctional molecule BTDSCN with TiO 2 The nanosheets are mixed and subjected to a hydrothermal reaction to form a benzothiadiazole-titanium dioxide nanosheet heterojunction composite photocatalytic material.
[0008] The present invention is also characterized in that:
[0009] In step 1, specifically:
[0010] Step 1.1, dissolving 2-bromo-9H-carbazole and sodium hydroxide in dimethyl sulfoxide, heating and stirring under argon protection, then adding methyl 3-bromopropionate, and continuing the reaction for 20-24 hours. After the reaction is completed, quench the reaction with water, acidify with hydrochloric acid to pH 5, stir for 1-2 hours, filter and wash to obtain compound 1;
[0011] Step 1.2, compound 1 and 2-trimethylsilylethanol are added to dichloromethane, cooled to 0°C under argon protection, EDCI and DMAP are added to react for 10-12 hours, and after the reaction is completed, the mixture is extracted with dichloromethane, and the organic layer is washed with saturated ammonium chloride solution, water, and saturated sodium chloride solution, dried with anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography to obtain compound 2;
[0012] Step 1.3, compound 2, bis(pinacol)diboron and potassium acetate were dissolved in N,N-dimethylformamide, and Pd(PPh 3 ) 2 Cl, heated at 80-90°C for 12-15h; after completion, cooled, extracted with ethyl acetate and water, washed the obtained organic phase with water and saturated sodium chloride solution, dried over anhydrous magnesium sulfate, filtered, collected the filtrate, and the solvent was rotary evaporated and the crude product was purified by silica gel chromatography to obtain compound 3;
[0013] Step 1.4, at 0°C, concentrated sulfuric acid, fuming nitric acid and fuming sulfuric acid are slowly added to 4,7-dibromobenzothiadiazole in sequence, followed by stirring in an ice-water bath for 0.5-1h, and then heating the reaction at 60-70°C for 6-8h; after the reaction, the solution is slowly poured into ice water, allowed to stand for 30-40min, filtered and washed, the resulting filter cake is a crude product, and the crude product is recrystallized to obtain compound 4;
[0014] Step 1.5, compound 4 and 2-tributylstannylthiophene are bubbled with argon in distilled tetrahydrofuran for 10 min, then heated to 90-100°C under the protection of argon and stirred for 20-30 min, and then Pd(PPh 3 ) 4, continue stirring and refluxing overnight, cool, add saturated potassium fluoride solution, stir at room temperature for 2-3 hours, filter the reaction mixture through a diatomaceous earth pad, wash the filter cake with dichloromethane, wash the obtained organic phase with water and saturated sodium chloride solution, dry over anhydrous sodium sulfate, filter, collect the filtrate, and then evaporate under reduced pressure to remove the solvent to obtain a crude product, which is recrystallized from ethyl acetate to obtain compound 5;
[0015] Step 1.6, compound 5 was dissolved in N,N-dimethylformamide, wrapped in tin foil to avoid light, and then heated and stirred at 80-90°C for 30-60 min, then NBS was added all at once and the reaction was continued in the dark with stirring for 3-4 h. At this time, there were still 3 points in the thin layer chromatography analysis, indicating incomplete conversion. Another portion of NBS was added and the reaction was continued with stirring for 6-8 h. When the thin layer chromatography analysis showed one point, the conversion was complete. The reaction solution was poured into ice water, and orange solid particles were precipitated. The filter cake was filtered and washed to obtain compound 6;
[0016] Step 1.7, compound 6 and compound 3 are dissolved in ultra-dry tetrahydrofuran, added to an aqueous potassium carbonate solution, bubbled with nitrogen for 10 min, then heated to 80-90°C and stirred for 30-40 min, and then Pd(dppf)Cl 2 ·CH 2 Cl 2 The reaction was allowed to proceed overnight, and after completion of the reaction, the organic phase was extracted and washed with water and saturated sodium chloride, dried over anhydrous sodium sulfate, filtered, and the solvent was rotary evaporated and the crude product was purified by silica gel chromatography to obtain the compound BTDSCO;
[0017] Step 1.8, dissolving the compound BTDSCO in a mixture of dichloromethane and methanol, then adding ammonium chloride, placing under argon protection, stirring at 40-50°C for 6-8h, then adding zinc powder in batches, and monitoring the reaction by thin layer chromatography. After the product conversion is complete, stop the reaction, extract with dichloromethane, wash the obtained organic phase with water and saturated sodium bicarbonate, dry with anhydrous sodium sulfate, filter, rotary evaporate the solvent and purify the crude product by silica gel chromatography to obtain BTDSCN.
[0018] In step 1.1, the heating and stirring temperature is 85-95° C., and the heating and stirring time is 30-40 min; the molar ratio of 2-bromo-9H-carbazole, sodium hydroxide, and methyl 3-bromopropionate is 1-2:5-10:2.5-5.
[0019] In step 1.2, the molar ratio of compound 1, 2-trimethylsilylethanol, EDCI and DMAP is 1-2: 2-5: 2-5: 0.1-0.2; in step 1.3, compound 2, bis(pinacol)diboron, potassium acetate and Pd(PPh 3 )2 The molar ratio of Cl is 1-2: 2-5: 2-5: 0.1-0.2; in the step 1.4, the molar ratio of concentrated sulfuric acid, fuming nitric acid, fuming sulfuric acid, and 4,7-dibromobenzothiadiazole is 3-5: 2-3: 1-2: 1-2.
[0020] In step 1.5, compound 4, 2-tributylstannylthiophene, Pd(PPh 3 ) 4 The molar ratio of compound 5, the first added NBS and the second added NBS is 1-2: 5-10: 5-10; in step 1.7, compound 6, compound 3 and Pd(dppf)Cl 2 ·CH 2 Cl 2 The molar ratio of is 1-2: 2-4: 0.1-0.2; in the step 1.8, the molar ratio of the compound BTDSCO, ammonium chloride and zinc powder is 1-2: 6-10: 10-15.
[0021] In step 2, specifically:
[0022] BTDSCN and TiO 2 The nanosheets were added to methanol, stirred for 30 min, ultrasonicated for 30 min to make them evenly dispersed, and the methanol was rotary evaporated. Then distilled water was added for hydrothermal reaction. After the reaction, the nanosheets were cooled, centrifuged, washed with deionized water for 4-5 times, and vacuum dried to obtain BTDSCN / TiO 2 The nanosheet heterojunction composite material is a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material.
[0023] BTDSCN and TiO 2 The molar ratio of the nanosheets is 0.05-0.1:1-2; the hydrothermal reaction temperature is 120-130°C, and the hydrothermal reaction time is 12-14h.
[0024] TiO 2 The preparation process of nanosheets is as follows:
[0025] Tetrabutyl titanate was added to the HF solution, stirred for 30 min, and then transferred to a stainless steel high-pressure reactor, reacted at 180-190 ° C for 24-36 h. After the reaction was completed, it was cooled, centrifuged, washed with deionized water 4-5 times, and vacuum dried to obtain TiO 2 Nanosheets.
[0026] The beneficial effect of the present invention is that BTDSCN / TiO2 can be obtained by using benzothiadiazole photofunctional molecules and titanium dioxide as raw materials through ultrasonic dispersion and hydrothermal method. 2The nanosheet heterojunction composite material is simple to operate and easy to implement, and the product is easy to separate and has a high yield. The obtained composite photocatalytic material has excellent photocatalytic degradation performance for organic dyes and can be applied to the field of sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The synthetic route of the benzothiadiazole photofunctional molecule of the present invention is as follows;
[0028] Figure 2a The BTDSCN / TiO 2 XRD pattern of nanosheet heterojunction composites;
[0029] Figure 2b The BTDSCN / TiO 2 XRD local magnification of nanosheet heterojunction composite material;
[0030] Figure 3 The BTDSCN / TiO 2 TEM image of nanosheet heterojunction composite material;
[0031] Figure 4 The BTDSCN / TiO 2 EPR images of nanosheet heterojunction composites;
[0032] Figure 5 The BTDSCN / TiO 2 Ultraviolet absorption diagram of photocatalytic removal of RhB and Cr(VI) by nanosheet heterojunction composites;
[0033] Figure 6 The BTDSCN / TiO 2 Degradation rate diagram of RhB removal from nanosheet heterojunction composites;
[0034] Figure 7 The BTDSCN / TiO 2 Degradation rate diagram of Cr(VI) removal from nanosheet heterojunction composites;
[0035] Figure 8 The BTDSCN / TiO 2 Experimental diagram of photocatalytic cycle of nanosheet heterojunction composite materials. DETAILED DESCRIPTION
[0036] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] The preparation method of the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material of the present invention is specifically implemented according to the following steps:
[0038] Step 1, synthesizing the benzothiadiazole photofunctional molecule BTDSCN; specifically:
[0039] Step 1.1, dissolving 2-bromo-9H-carbazole and sodium hydroxide in dimethyl sulfoxide, heating and stirring under argon protection, the heating and stirring temperature is 85-95° C., and the heating and stirring time is 30-40 min; then adding methyl 3-bromopropionate, continuing the reaction for 20-24 h, quenching the reaction with water after the reaction is completed, and then acidifying the reactant with 2 mol / L hydrochloric acid to pH 5, stirring at room temperature for 1-2 h, filtering with suction, and washing the filter cake with methanol to obtain a white solid, which is compound 1;
[0040] The molar ratio of 2-bromo-9H-carbazole, sodium hydroxide and methyl 3-bromopropionate is 1-2:5-10:2.5-5;
[0041] Step 1.2, compound 1 and 2-trimethylsilylethanol are added to dichloromethane, cooled to 0°C under argon protection, and then EDCI and DMAP are added to the mixture solution, followed by reaction at room temperature for 10-12 hours. After the reaction is completed, extraction is performed with dichloromethane, and the organic layer is washed with saturated ammonium chloride solution, water, and saturated sodium chloride solution, dried over anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography (PE:EA=20:1, v / v) to obtain a yellow oil, which is compound 2;
[0042] The molar ratio of compound 1, 2-trimethylsilylethanol, EDCI and DMAP is 1-2: 2-5: 2-5: 0.1-0.2;
[0043] Step 1.3, compound 2, bis(pinacol)diboron and potassium acetate were dissolved in N,N-dimethylformamide, and Pd(PPh 3 ) 2 Cl, heating reaction, heating temperature is 80-90 ℃, heating time is 12-15h; after the reaction, cool to room temperature, extract with ethyl acetate and water, wash the obtained organic phase with water and saturated sodium chloride solution, dry over anhydrous magnesium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product by silica gel chromatography (PE:EA=20:1, v / v) to obtain a colorless oil, which is compound 3;
[0044] Compound 2, bis(pinacol)diboron, potassium acetate and Pd(PPh 3 ) 2 The molar ratio of Cl is 1-2:2-5:2-5:0.1-0.2;
[0045] Step 1.4, at 0°C, concentrated sulfuric acid, fuming nitric acid and fuming sulfuric acid are slowly added to 4,7-dibromobenzothiadiazole in sequence, and then stirred in an ice-water bath at a temperature of -5 to 0°C for 0.5 to 1 h, and then heated to react at a temperature of 60 to 70°C for 6 to 8 h; after the reaction, the solution is slowly poured into ice water, allowed to stand for 30 to 40 min, filtered with a Buchner funnel, and the filter cake is washed with distilled water. The obtained filter cake is a crude product, and the crude product is recrystallized to obtain a slightly yellow product, which is compound 4;
[0046] The molar ratio of concentrated sulfuric acid, fuming nitric acid, fuming sulfuric acid and 4,7-dibromobenzothiadiazole is 3-5:2-3:1-2:1-2;
[0047] Step 1.5, compound 4 and 2-tributylstannylthiophene are bubbled with argon in distilled tetrahydrofuran for 10 min, then heated to 90-100°C under the protection of argon and stirred for 20-30 min, and then Pd(PPh 3 ) 4 , continue stirring and refluxing overnight, after cooling, add saturated potassium fluoride solution, stir at room temperature for 2-3h, filter the reaction mixture through a diatomaceous earth pad, wash the filter cake with dichloromethane, wash the obtained organic phase with water and saturated sodium chloride solution, dry over anhydrous sodium sulfate, filter, collect the filtrate, and then evaporate under reduced pressure to remove the solvent to obtain a crude product, which is recrystallized from ethyl acetate to obtain an orange solid powder product, which is compound 5;
[0048] Compound 4, 2-tributylstannylthiophene, Pd(PPh 3 ) 4 The molar ratio is 1-2:2.5-5:0.1-0.2;
[0049] Step 1.6, dissolve compound 5 in N,N-dimethylformamide, wrap it with tin foil to avoid light, and then heat and stir at 80-90°C for 30-60min, then add NBS all at once and continue stirring in the dark for 3-4h. At this time, there are still 3 points in the thin layer chromatography analysis, which means that the conversion is not complete. Add another portion of NBS and continue stirring the reaction for 6-8h. When the thin layer chromatography analysis shows one point, the conversion is complete. Pour the reaction solution into ice water, and orange solid particles precipitate. Filter with a Buchner funnel, wash the filter cake with water, and the obtained orange-red solid is compound 6;
[0050] The molar ratio of compound 5, NBS added for the first time, and NBS added for the second time is 1-2:5-10:5-10;
[0051] Step 1.7, compound 6 and compound 3 are dissolved in ultra-dry tetrahydrofuran, added to an aqueous potassium carbonate solution, bubbled with nitrogen for 10 min, then the system is heated to 80-90°C and stirred for 30-40 min, and then Pd(dppf)Cl is added 2 ·CH 2 Cl 2 , react at 80-90°C overnight, extract with dichloromethane after the reaction, wash the collected organic phase with water and saturated sodium chloride, dry with anhydrous sodium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product by silica gel chromatography (DCM: Hex = 2: 1, v / v) to obtain a dark red solid powder, which is the compound BTDSCO;
[0052] Compound 6, compound 3 and Pd(dppf)Cl 2 ·CH 2 Cl 2 The molar ratio is 1-2:2-4:0.1-0.2;
[0053] Step 1.8, dissolving the compound BTDSCO in a mixture of dichloromethane and methanol, then adding ammonium chloride, placing under argon protection, stirring the reaction, the reaction temperature is 40-50°C, and the reaction time is 6-8h; then zinc powder is added in batches, and the reaction is monitored by thin layer chromatography analysis. After the product conversion is complete, the reaction is stopped, extracted with dichloromethane, and the obtained organic phase is washed with water and saturated sodium bicarbonate, dried over anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography (EA:PE=2:1, v / v) to obtain a yellow-brown solid powder, which is the target product BTDSCN.
[0054] The molar ratio of the compound BTDSCO, ammonium chloride and zinc powder is 1-2:6-10:10-15;
[0055] Step 2: Combine benzothiadiazole photofunctional molecules with TiO 2 The nanosheets are mixed and subjected to a hydrothermal reaction to form a benzothiadiazole-titanium dioxide nanosheet heterojunction composite photocatalytic material;
[0056] Specifically: BTDSCN and TiO 2 The nanosheets were added to methanol, stirred for 30 min at room temperature, and ultrasonicated for 30 min to make them evenly dispersed. The methanol was then rotary evaporated, and distilled water was added. The mixture was transferred to a stainless steel reactor for hydrothermal reaction at a reaction temperature of 120-130 ° C and a reaction time of 12-14 h. After the reaction, the mixture was cooled to room temperature, and the precipitate was collected by high-speed centrifugation, washed with deionized water for 4-5 times, and vacuum dried to obtain dark gray BTDSCN / TiO 2The nanosheet heterojunction composite material is a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material;
[0057] BTDSCN and TiO 2 The molar ratio of nanosheets is 0.05-0.1:1-2;
[0058] Among them, TiO 2 The preparation process of the nanosheets is as follows: tetrabutyl titanate is added to the HF solution, stirred for 30 minutes, and then transferred to a stainless steel high-pressure reactor, reacted at 180-190°C for 24-36 hours. After the reaction is completed, it is cooled to room temperature, and the precipitate is collected by high-speed centrifugation, washed with deionized water for 4-5 times, and vacuum dried to obtain white TiO 2 Nanosheets.
[0059] The benzothiadiazole-titanium dioxide nanosheet heterojunction composite material prepared by the method of the present invention can be used in the photocatalytic degradation of organic pollutants, has excellent photocatalytic degradation ability, has good catalytic degradation effect on organic pollutants and heavy metal ions, and can be used in the fields of sewage treatment. The organic pollutant is an organic dye, the organic dye includes rhodamine B, and the heavy metal ion is Cr(VI).
[0060] Example 1
[0061] The preparation method of the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material of the present invention is specifically implemented according to the following steps:
[0062] Step 1, synthesizing the benzothiadiazole photofunctional molecule BTDSCN; specifically:
[0063] Step 1.1, dissolving 2-bromo-9H-carbazole and sodium hydroxide in dimethyl sulfoxide, heating and stirring under argon protection, the heating and stirring temperature is 90°C, and the heating and stirring time is 30 minutes; then adding methyl 3-bromopropionate, continuing the reaction for 24 hours, quenching the reaction with water after the reaction is completed, and then acidifying the reactant with 2 mol / L hydrochloric acid to pH 5, stirring at room temperature for 2 hours, filtering with suction, and washing the filter cake with methanol to obtain compound 1;
[0064] The molar ratio of 2-bromo-9H-carbazole, sodium hydroxide, and methyl 3-bromopropionate is 1:5:2.5;
[0065] Step 1.2, compound 1 and 2-trimethylsilylethanol are added to dichloromethane, cooled to 0°C under argon protection, and then EDCI and DMAP are added to the mixture solution, followed by reaction at room temperature for 12 hours. After the reaction is completed, extraction is performed with dichloromethane, and the organic layer is washed with saturated ammonium chloride solution, water, and saturated sodium chloride solution, dried with anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography to obtain compound 2;
[0066] The molar ratio of compound 1, 2-trimethylsilylethanol, EDCI, and DMAP was 1:2:2:0.1;
[0067] Step 1.3, compound 2, bis(pinacol)diboron and potassium acetate were dissolved in N,N-dimethylformamide, and Pd(PPh 3 ) 2 Cl, heating reaction, heating temperature is 80 ℃, heating time is 12h; after the reaction, cool to room temperature, extract with ethyl acetate and water, wash the obtained organic phase with water and saturated sodium chloride solution, dry with anhydrous magnesium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product with silica gel chromatography to obtain a colorless oily substance, which is compound 3;
[0068] Compound 2, bis(pinacol)diboron, potassium acetate and Pd(PPh 3 ) 2 The molar ratio of Cl is 1:2:2:0.2;
[0069] Step 1.4, at 0°C, concentrated sulfuric acid, fuming nitric acid and fuming sulfuric acid are slowly added to 4,7-dibromobenzothiadiazole in sequence, and then stirred in an ice-water bath at 0°C for 0.5 h, and then heated to react at 60°C for 6 h; after the reaction, the solution is slowly poured into ice water, allowed to stand for 30 min, filtered with a Buchner funnel, and the filter cake is washed with distilled water. The obtained filter cake is a crude product, and the crude product is recrystallized to obtain a slightly yellow product, which is compound 4;
[0070] The molar ratio of concentrated sulfuric acid, fuming nitric acid, fuming sulfuric acid, and 4,7-dibromobenzothiadiazole is 3:2:1:1;
[0071] Step 1.5, compound 4 and 2-tributylstannylthiophene were bubbled with argon in distilled tetrahydrofuran for 10 min, then heated to 90°C and stirred for 30 min under the protection of argon, and then Pd(PPh 3 ) 4, continue stirring and refluxing overnight, after cooling, add saturated potassium fluoride solution, stir at room temperature for 2h, filter the reaction mixture through a diatomaceous earth pad, wash the filter cake with dichloromethane, wash the obtained organic phase with water and saturated sodium chloride solution, dry over anhydrous sodium sulfate, filter, collect the filtrate, and then evaporate under reduced pressure to remove the solvent to obtain a crude product, which is recrystallized from ethyl acetate to obtain an orange solid powder product, which is compound 5;
[0072] Compound 4, 2-tributylstannylthiophene, Pd(PPh 3 ) 4 The molar ratio is 1:2.5:0.1;
[0073] Step 1.6, compound 5 was dissolved in N,N-dimethylformamide, wrapped in tin foil to avoid light, and then heated and stirred at 80°C for 30 minutes. NBS was then added all at once and the reaction was continued in the dark with stirring for 4 hours. At this time, there were still 3 points in the thin layer chromatography analysis, indicating incomplete conversion. Another portion of NBS was added and the reaction was continued with stirring for 8 hours. When the thin layer chromatography analysis showed one point, the conversion was complete. The reaction solution was poured into ice water, and orange solid particles were precipitated. The mixture was filtered and the filter cake was washed with water. The obtained orange-red solid was compound 6;
[0074] The molar ratio of compound 5, NBS added for the first time, and NBS added for the second time was 1:5:5;
[0075] Step 1.7, compound 6 and compound 3 were dissolved in ultra-dry tetrahydrofuran, added to an aqueous potassium carbonate solution, and nitrogen was bubbled for 10 min. The system was then heated to 80 °C and stirred for 30 min. Pd(dppf)Cl was then added. 2 ·CH 2 Cl 2 , react at 80°C overnight, extract with dichloromethane after the reaction is completed, wash the collected organic phase with water and saturated sodium chloride, dry with anhydrous sodium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product by silica gel chromatography to obtain a dark red solid powder, which is the compound BTDSCO;
[0076] Compound 6, compound 3 and Pd(dppf)Cl 2 ·CH 2 Cl 2 The molar ratio is 1:2:0.1;
[0077] Step 1.8, dissolving the compound BTDSCO in a mixture of dichloromethane and methanol, then adding ammonium chloride, placing under argon protection, stirring the reaction, the reaction temperature is 40°C, and the reaction time is 6 hours; then zinc powder is added in batches, and the reaction is monitored by thin layer chromatography analysis. After the product conversion is complete, the reaction is stopped, extracted with dichloromethane, and the obtained organic phase is washed with water and saturated sodium bicarbonate, dried over anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography to obtain a yellow-brown solid powder, which is the target product BTDSCN.
[0078] The molar ratio of compound BTDSCO, ammonium chloride, and zinc powder is 1:6:10;
[0079] Step 2: BTDSCN and TiO 2 The nanosheets were added to methanol, stirred for 30 min at room temperature, and ultrasonicated for 30 min to make them evenly dispersed. The methanol was then rotary evaporated, and distilled water was added. The mixture was transferred to a stainless steel reactor for hydrothermal reaction at 120 °C for 12 h. After the reaction, the mixture was cooled to room temperature, and the precipitate was collected by high-speed centrifugation, washed with deionized water 4 times, and vacuum dried to obtain dark gray BTDSCN / TiO 2 The nanosheet heterojunction composite material is a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material;
[0080] BTDSCN and TiO 2 The molar ratio of nanosheets was 0.05:1;
[0081] Among them, TiO 2 The preparation process of the nanosheets is as follows: tetrabutyl titanate is added to the HF solution, stirred for 30 minutes, and then transferred to a stainless steel autoclave for reaction at 180°C for 24 hours. After the reaction is completed, the solution is cooled to room temperature, and the precipitate is collected by high-speed centrifugation, washed with deionized water for 4 times, and then vacuum dried to obtain TiO 2 Nanosheets.
[0082] Example 2
[0083] The preparation method of the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material of the present invention is specifically implemented according to the following steps:
[0084] Step 1, synthesizing the benzothiadiazole photofunctional molecule BTDSCN; specifically:
[0085] Step 1.1, dissolving 2-bromo-9H-carbazole and sodium hydroxide in dimethyl sulfoxide, heating and stirring under argon protection, the heating and stirring temperature is 85°C, and the heating and stirring time is 30 minutes; then adding methyl 3-bromopropionate, continuing the reaction for 20 hours, quenching the reaction with water after the reaction is completed, and then acidifying the reactant with 2 mol / L hydrochloric acid to pH 5, stirring at room temperature for 1 hour, filtering with suction, and washing the filter cake with methanol to obtain a white solid, which is compound 1;
[0086] The molar ratio of 2-bromo-9H-carbazole, sodium hydroxide, and methyl 3-bromopropionate is 2:5:2.5;
[0087] Step 1.2, compound 1 and 2-trimethylsilylethanol are added to dichloromethane, cooled to 0°C under argon protection, and then EDCI and DMAP are added to the mixture solution, followed by reaction at room temperature for 10 hours. After the reaction is completed, extraction is performed with dichloromethane, and the organic layer is washed with saturated ammonium chloride solution, water, and saturated sodium chloride solution, dried with anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography to obtain compound 2;
[0088] The molar ratio of compound 1, 2-trimethylsilylethanol, EDCI, and DMAP is 2:2:2:0.1;
[0089] Step 1.3, compound 2, bis(pinacol)diboron and potassium acetate were dissolved in N,N-dimethylformamide, and Pd(PPh 3 ) 2 Cl, heating reaction, heating temperature is 80 ℃, heating time is 12h; after the reaction, cool to room temperature, extract with ethyl acetate and water, wash the obtained organic phase with water and saturated sodium chloride solution, dry with anhydrous magnesium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product with silica gel chromatography to obtain a colorless oily substance, which is compound 3;
[0090] Compound 2, bis(pinacol)diboron, potassium acetate and Pd(PPh 3 ) 2 The molar ratio of Cl is 2:3:3:0.1;
[0091] Step 1.4, at 0°C, concentrated sulfuric acid, fuming nitric acid and fuming sulfuric acid are slowly added to 4,7-dibromobenzothiadiazole in sequence, and then stirred in an ice-water bath at -3°C for 1 hour, and then heated to react at 60°C for 6 hours; after the reaction, the solution is slowly poured into ice water, allowed to stand for 35 minutes, filtered with a Buchner funnel, and the filter cake is washed with distilled water. The obtained filter cake is a crude product, and the crude product is recrystallized to obtain a slightly yellow product, which is compound 4;
[0092] The molar ratio of concentrated sulfuric acid, fuming nitric acid, fuming sulfuric acid, and 4,7-dibromobenzothiadiazole is 3:2:2:2;
[0093] Step 1.5, compound 4 and 2-tributylstannylthiophene were bubbled with argon in distilled tetrahydrofuran for 10 min, then heated to 100 °C and stirred for 20 min under the protection of argon, and then Pd(PPh 3 ) 4 , continue stirring and refluxing overnight, after cooling, add saturated potassium fluoride solution, stir at room temperature for 2.5h, filter the reaction mixture through a diatomaceous earth pad, wash the filter cake with dichloromethane, wash the obtained organic phase with water and saturated sodium chloride solution, dry over anhydrous sodium sulfate, filter, collect the filtrate, and then evaporate under reduced pressure to remove the solvent to obtain a crude product, which is recrystallized from ethyl acetate to obtain an orange solid powder product, which is compound 5;
[0094] Compound 4, 2-tributylstannylthiophene, Pd(PPh 3 ) 4 The molar ratio is 2:2.5:0.1;
[0095] Step 1.6, compound 5 was dissolved in N,N-dimethylformamide, wrapped in tin foil to avoid light, and then heated and stirred at 80°C for 40 minutes. NBS was then added all at once and the reaction was continued in the dark with stirring for 3 hours. At this time, there were still 3 points in the thin layer chromatography analysis, indicating incomplete conversion. Another portion of NBS was added and the reaction was continued with stirring for 7 hours. When the thin layer chromatography analysis showed one point, the conversion was complete. The reaction solution was poured into ice water, and solid particles were precipitated. The mixture was filtered with a Buchner funnel, and the filter cake was washed with water. The obtained orange-red solid was compound 6;
[0096] The molar ratio of compound 5, NBS added for the first time, and NBS added for the second time was 1:6:6;
[0097] Step 1.7, compound 6 and compound 3 were dissolved in ultra-dry tetrahydrofuran, added to an aqueous potassium carbonate solution, bubbled with nitrogen for 10 min, then the system was heated to 90 °C and stirred for 35 min, and then Pd(dppf)Cl was added 2 ·CH 2 Cl 2 , react at 90°C overnight, extract with dichloromethane after the reaction is completed, wash the collected organic phase with water and saturated sodium chloride, dry with anhydrous sodium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product by silica gel chromatography to obtain a dark red solid powder, which is the compound BTDSCO;
[0098] Compound 6, compound 3 and Pd(dppf)Cl2 ·CH 2 Cl 2 The molar ratio is 2:3:0.1;
[0099] Step 1.8, dissolving the compound BTDSCO in a mixture of dichloromethane and methanol, then adding ammonium chloride, placing under argon protection, stirring the reaction, the reaction temperature is 50°C, and the reaction time is 6 hours; then adding zinc powder in batches, monitoring the reaction by thin layer chromatography analysis, after the product conversion is complete, stopping the reaction, extracting with dichloromethane, washing the obtained organic phase with water and saturated sodium bicarbonate, drying over anhydrous sodium sulfate, filtering, rotary evaporating the solvent and purifying the crude product by silica gel chromatography to obtain BTDSCN.
[0100] The molar ratio of compound BTDSCO, ammonium chloride, and zinc powder is 2:7:12;
[0101] Step 2: BTDSCN and TiO 2 The nanosheets were added to methanol, stirred for 30 min at room temperature, and ultrasonicated for 30 min to make them evenly dispersed. The methanol was then rotary evaporated, and distilled water was added. The mixture was transferred to a stainless steel reactor for hydrothermal reaction at 120 °C for 14 h. After the reaction, the mixture was cooled to room temperature, and the precipitate was collected by high-speed centrifugation, washed with deionized water 5 times, and vacuum dried to obtain dark gray BTDSCN / TiO 2 Nanosheet heterojunction composites;
[0102] BTDSCN and TiO 2 The molar ratio of nanosheets is 0.05:2;
[0103] Among them, TiO 2 The preparation process of the nanosheets is as follows: tetrabutyl titanate is added to the HF solution, stirred for 30 minutes, and then transferred to a stainless steel autoclave for reaction at 180°C for 28 hours. After the reaction is completed, the solution is cooled to room temperature, and the precipitate is collected by high-speed centrifugation, washed with deionized water for 5 times, and then vacuum dried to obtain TiO 2 Nanosheets.
[0104] Example 3
[0105] The preparation method of the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material of the present invention is specifically implemented according to the following steps:
[0106] Step 1, synthesizing the benzothiadiazole photofunctional molecule BTDSCN; specifically:
[0107] Step 1.1, dissolving 2-bromo-9H-carbazole and sodium hydroxide in dimethyl sulfoxide, heating and stirring under argon protection, the heating and stirring temperature is 95° C., and the heating and stirring time is 40 min; then adding methyl 3-bromopropionate, continuing the reaction for 24 h, quenching the reaction with water after the reaction is completed, and then acidifying the reactant with 2 mol / L hydrochloric acid to pH 5, stirring at room temperature for 2 h, filtering with suction, and washing the filter cake with methanol to obtain a white solid, which is compound 1;
[0108] The molar ratio of 2-bromo-9H-carbazole, sodium hydroxide, and methyl 3-bromopropionate is 2:10:2.5;
[0109] Step 1.2, compound 1 and 2-trimethylsilylethanol are added to dichloromethane, cooled to 0°C under argon protection, and then EDCI and DMAP are added to the mixture solution, followed by reaction at room temperature for 12 hours. After the reaction is completed, extraction is performed with dichloromethane, and the organic layer is washed with saturated ammonium chloride solution, water, and saturated sodium chloride solution, dried with anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography to obtain compound 2;
[0110] The molar ratio of compound 1, 2-trimethylsilylethanol, EDCI, and DMAP is 2:5:5:0.2;
[0111] Step 1.3, compound 2, bis(pinacol)diboron and potassium acetate were dissolved in N,N-dimethylformamide, and Pd(PPh 3 ) 2 Cl, heating reaction, heating temperature is 90 ℃, heating time is 15h; after the reaction, cool to room temperature, extract with ethyl acetate and water, wash the obtained organic phase with water and saturated sodium chloride solution, dry with anhydrous magnesium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product with silica gel chromatography to obtain a colorless oily substance, which is compound 3;
[0112] Compound 2, bis(pinacol)diboron, potassium acetate and Pd(PPh 3 ) 2 The molar ratio of Cl is 2:5:5:0.2;
[0113] Step 1.4, at 0°C, concentrated sulfuric acid, fuming nitric acid and fuming sulfuric acid are slowly added to 4,7-dibromobenzothiadiazole in sequence, and then stirred in an ice-water bath at -5°C for 1 hour, and then heated to react at 70°C for 8 hours; after the reaction, the solution is slowly poured into ice water, allowed to stand for 40 minutes, filtered with a Buchner funnel, and the filter cake is washed with distilled water. The filter cake is the crude product, and the crude product is recrystallized to obtain a slightly yellow product, which is compound 4;
[0114] The molar ratio of concentrated sulfuric acid, fuming nitric acid, fuming sulfuric acid, and 4,7-dibromobenzothiadiazole is 5:3:2:2;
[0115] Step 1.5, compound 4 and 2-tributylstannylthiophene were bubbled with argon in distilled tetrahydrofuran for 10 min, then heated to 100 °C and stirred for 30 min under the protection of argon, and then Pd(PPh 3 ) 4 , continue stirring and refluxing overnight, after cooling, add saturated potassium fluoride solution, stir at room temperature for 3 hours, filter the reaction mixture through a diatomaceous earth pad, wash the filter cake with dichloromethane, wash the obtained organic phase with water and saturated sodium chloride solution, dry over anhydrous sodium sulfate, filter, collect the filtrate, and then evaporate under reduced pressure to remove the solvent to obtain a crude product, which is recrystallized from ethyl acetate to obtain an orange solid powder product, which is compound 5;
[0116] Compound 4, 2-tributylstannylthiophene, Pd(PPh 3 ) 4 The molar ratio is 2:5:0.2;
[0117] Step 1.6, compound 5 was dissolved in N,N-dimethylformamide, wrapped in tin foil to avoid light, and then heated and stirred at 90°C for 60 minutes. NBS was then added all at once and the reaction was continued in the dark with stirring for 4 hours. At this time, there were still 3 points in the thin layer chromatography analysis, indicating incomplete conversion. Another portion of NBS was added and the reaction was continued with stirring for 8 hours. When the thin layer chromatography analysis showed one point, the conversion was complete. The reaction solution was poured into ice water, and solid particles were precipitated. The mixture was filtered with a Buchner funnel, and the filter cake was washed with water. The obtained orange-red solid was compound 6;
[0118] The molar ratio of compound 5, NBS added for the first time, and NBS added for the second time was 2:10:10;
[0119] Step 1.7, compound 6 and compound 3 were dissolved in ultra-dry tetrahydrofuran, added to an aqueous potassium carbonate solution, bubbled with nitrogen for 10 min, then the system was heated to 90 °C and stirred for 40 min, and then Pd(dppf)Cl was added 2 ·CH 2 Cl 2 , react at 90°C overnight, extract with dichloromethane after the reaction is completed, wash the collected organic phase with water and saturated sodium chloride, dry with anhydrous sodium sulfate, filter, collect the filtrate, rotary evaporate the solvent and purify the crude product by silica gel chromatography to obtain a dark red solid powder, which is the compound BTDSCO;
[0120] Compound 6, compound 3 and Pd(dppf)Cl 2·CH 2 Cl 2 The molar ratio is 2:4:0.2;
[0121] Step 1.8, dissolving the compound BTDSCO in a mixture of dichloromethane and methanol, then adding ammonium chloride, placing under argon protection, stirring the reaction, the reaction temperature is 50°C, and the reaction time is 8 hours; then adding zinc powder in batches, monitoring the reaction by thin layer chromatography analysis, after the product conversion is complete, stopping the reaction, extracting with dichloromethane, washing the obtained organic phase with water and saturated sodium bicarbonate, drying over anhydrous sodium sulfate, filtering, rotary evaporating the solvent and purifying the crude product by silica gel chromatography to obtain a yellow-brown solid powder, namely BTDSCN.
[0122] The molar ratio of compound BTDSCO, ammonium chloride, and zinc powder is 2:10:15;
[0123] Step 2: BTDSCN and TiO 2 The nanosheets were added to methanol, stirred for 30 min at room temperature, and ultrasonicated for 30 min to make them evenly dispersed. The methanol was then rotary evaporated, and distilled water was added. The mixture was transferred to a stainless steel reactor for hydrothermal reaction at 130 °C for 14 h. After the reaction, the mixture was cooled to room temperature, and the precipitate was collected by high-speed centrifugation, washed with deionized water 5 times, and vacuum dried to obtain dark gray BTDSCN / TiO 2 Nanosheet heterojunction composites;
[0124] BTDSCN and TiO 2 The molar ratio of nanosheets is 0.1:2;
[0125] Among them, TiO 2 The preparation process of the nanosheets is as follows: tetrabutyl titanate is added to the HF solution, stirred for 30 minutes, and then transferred to a stainless steel high-pressure reactor, reacted at 190°C for 36 hours. After the reaction is completed, it is cooled to room temperature, and the precipitate is collected by high-speed centrifugation, washed with deionized water for 5 times, and then vacuum dried to obtain TiO 2 Nanosheets.
[0126] The product obtained by the method of the present invention was analyzed by HRTEM, XPS, FTIR and the like to verify the accuracy of the heterojunction formation. From the test results, it can be seen that the heterojunction was successfully prepared.
[0127] Depend on Figure 2a and Figure 2b It can be seen that TiO 2 Nanosheets and BTDSCN / TiO 2The nanosheet heterojunction composite material has the same diffraction peaks, which correspond to the JCPDS No.1-1272 standard card of anatase, indicating that TiO 2 The crystal structure of BTDSCN / TiO 2 Compared with TiO 2 The diffraction peak of the TiO2 has an obvious left shift. The shift of the diffraction peak may be due to the formation of the heterojunction slightly affecting the 2 The crystal structure of BTDSCN / TiO 2 Successful preparation of nanosheet heterojunction composites.
[0128] Depend on Figure 3 It can be seen that BTDSCN / TiO 2 The structure of the nanosheet heterojunction composite material is a surface dispersed heterojunction, BTDSCN and TiO 2 The surfaces are closely connected and have a large contact area, which can enhance the transfer efficiency of photogenerated carriers and significantly improve their photocatalytic performance.
[0129] Depend on Figure 4 It can be seen that pure TiO 2 The nanosheet has a very weak V at g = 2.004 O signal. 2 The nanosheet heterojunction composite shows an obvious V O signal, which indicates that BTDSCN / TiO 2 Nanosheet heterojunction composites introduce V O Oxygen vacancies can effectively regulate the electronic structure of the catalyst surface and enhance the electron enrichment effect. On the one hand, it can promote the absorption of visible light and improve the utilization rate of solar energy. On the other hand, it can change the charge transfer ability of the material and reduce the recombination of electron-hole pairs. Figure 5 It can be seen that under light conditions, BTDSCN / TiO 2 The nanosheet heterojunction composite material has a significant effect on the removal of RhB and Cr(VI) within 90 minutes.
[0130] A 300W xenon lamp was used as the light source (with an ultraviolet filter (λ>420nm)). 20mg TiO 2 Nanosheets, commercial TiO 2 Material (P25) or BTDSCN / TiO 2 The heterojunction composite material was dispersed in 25 mL RhB (20 mg L -1 ) and 25mL Cr(VI)(40mgL -1 , use K 2 Cr2 O 7 The mixture was stirred for 30 minutes in the dark to reach adsorption-desorption equilibrium, and then placed under a xenon lamp for 90 minutes. During this period, 2 mL of the upper suspension was collected every 10 minutes. The collected liquid was centrifuged at 12000 rpm in a high-speed centrifuge to obtain a clear solution, and its absorbance was tested by a UV-visible spectrophotometer to deduce the content of RhB and Cr(VI) in the collected solution. The absorption wavelengths of RhB and Cr(VI) in aqueous solution are λ max They are 554nm and 356nm respectively.
[0131] Depend on Figure 6 and Figure 7 It can be seen that after 90 min of visible light irradiation, the degradation of RhB and the reduction of Cr(VI) were 92.1% and 74.8%, respectively. 2 The degradation effect of nanosheet heterojunction composites on RhB is as good as that of pure TiO 2 BTDSCN / TiO 2 The degradation effect of nanosheet heterojunction composites on Cr(VI) is comparable to that of pure TiO 2 About 7 times of Figure 8 It can be seen that BTDSCN / TiO 2 After being recycled four times, the catalyst of the nanosheet heterojunction composite material still exhibited good photocatalytic activity, showing good recyclability.
Claims
1. A method for preparing a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material, characterized in that: Follow the steps below to implement it: Step 1, synthesizing the benzothiadiazole photofunctional molecule BTDSCN; specifically: Step 1.1, dissolving 2-bromo-9H-carbazole and sodium hydroxide in dimethyl sulfoxide, heating and stirring under argon protection, then adding methyl 3-bromopropionate, and continuing the reaction for 20-24 hours. After the reaction is completed, quench the reaction with water, acidify with hydrochloric acid to pH 5, stir for 1-2 hours, filter and wash to obtain compound 1; Step 1.2, compound 1 and 2-trimethylsilylethanol are added to dichloromethane, cooled to 0°C under argon protection, EDCI and DMAP are added to react for 10-12h, and after the reaction is completed, the mixture is extracted with dichloromethane, and the organic layer is washed with saturated ammonium chloride solution, water, and saturated sodium chloride solution, dried over anhydrous sodium sulfate, filtered, and the solvent is rotary evaporated and the crude product is purified by silica gel chromatography to obtain compound 2; Step 1.3, dissolving compound 2, bis(pinacol)diboron and potassium acetate in N,N-dimethylformamide, adding Pd(PPh3)2Cl under argon protection, and heating at 80-90°C for 12-15h; after completion, cooling, extracting with ethyl acetate and water, washing the obtained organic phase with water and saturated sodium chloride solution, drying over anhydrous magnesium sulfate, filtering, collecting the filtrate, rotary evaporating the solvent, and purifying the crude product by silica gel chromatography to obtain compound 3; Step 1.4, at 0°C, concentrated sulfuric acid, fuming nitric acid and fuming sulfuric acid are slowly added to 4,7-dibromobenzothiadiazole in sequence, followed by stirring in an ice-water bath for 0.5-1h, and then heating the reaction at 60-70°C for 6-8h; after the reaction, the solution is slowly poured into ice water, allowed to stand for 30-40min, filtered and washed, the resulting filter cake is a crude product, and the crude product is recrystallized to obtain compound 4; Step 1.5, compound 4 and 2-tributylstannylthiophene are bubbled with argon in distilled tetrahydrofuran for 10 min, then heated to 90-100°C under the protection of argon and stirred for 20-30 min, then Pd(PPh3)4 is added, stirring and reflux are continued overnight, cooled, saturated potassium fluoride solution is added, and stirred at room temperature for 2-3 h, the reaction mixture is filtered through a diatomaceous earth pad, the filter cake is washed with dichloromethane, the obtained organic phase is washed with water and saturated sodium chloride solution, dried over anhydrous sodium sulfate, filtered, the filtrate is collected, and then the solvent is evaporated under reduced pressure to obtain a crude product, and the crude product is recrystallized from ethyl acetate to obtain compound 5; Step 1.6, compound 5 was dissolved in N,N-dimethylformamide, wrapped in tin foil to avoid light, and then heated and stirred at 80-90°C for 30-60 min, then NBS was added all at once and the reaction was continued in the dark with stirring for 3-4 h. At this time, there were still 3 points in the thin layer chromatography analysis, indicating incomplete conversion. Another portion of NBS was added and the reaction was continued with stirring for 6-8 h. When the thin layer chromatography analysis showed one point, the conversion was complete. The reaction solution was poured into ice water, and orange solid particles were precipitated. The filter cake was filtered and washed to obtain compound 6; Step 1.7, compound 6 and compound 3 are dissolved in ultra-dry tetrahydrofuran, added to a potassium carbonate aqueous solution, bubbled with nitrogen for 10 min, then heated to 80-90°C and stirred for 30-40 min, then Pd(dppf)Cl2·CH2Cl2 is added to react overnight, after the reaction is completed, the organic phase is extracted, washed with water and saturated sodium chloride, dried over anhydrous sodium sulfate, filtered, the solvent is rotary evaporated, and the crude product is purified by silica gel chromatography to obtain compound BTDSCO; Step 1.8, dissolving the compound BTDSCO in a mixture of dichloromethane and methanol, then adding ammonium chloride, placing under argon protection, stirring at 40-50°C for 6-8h, then adding zinc powder in batches, monitoring the reaction by thin layer chromatography analysis, and stopping the reaction after the product conversion is complete, extracting with dichloromethane, washing the obtained organic phase with water and saturated sodium bicarbonate, drying over anhydrous sodium sulfate, filtering, rotary evaporating the solvent, and purifying the crude product by silica gel chromatography to obtain BTDSCN; Step 2: Mix the benzothiadiazole photofunctional molecule BTDSCN with TiO2 nanosheets and perform a hydrothermal reaction to form a benzothiadiazole-titanium dioxide nanosheet heterojunction composite photocatalytic material.
2. The method for preparing the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material according to claim 1, characterized in that: In the step 1.1, the heating and stirring temperature is 85-95° C., and the heating and stirring time is 30-40 min. The molar ratio of 2-bromo-9H-carbazole, sodium hydroxide, and methyl 3-bromopropionate is 1-2:5-10:2.5-5.
3. The method for preparing the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material according to claim 1, characterized in that: In the step 1.2, the molar ratio of compound 1, 2-trimethylsilylethanol, EDCI and DMAP is 1-2: 2-5: 2-5: 0.1-0.2; in the step 1.3, the molar ratio of compound 2, bis(pinacol)diboron, potassium acetate and Pd(PPh3)2Cl is 1-2: 2-5: 2-5: 0.1-0.2; in the step 1.4, the molar ratio of concentrated sulfuric acid, fuming nitric acid, fuming sulfuric acid and 4,7-dibromobenzothiadiazole is 3-5: 2-3: 1-2: 1-2.
4. The method for preparing the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material according to claim 3, characterized in that: In the step 1.5, the molar ratio of compound 4, 2-tributylstannylthiophene and Pd(PPh3)4 is 1-2:2.5-5:0.1-0.2; in the step 1.6, the molar ratio of compound 5, NBS added for the first time and NBS added for the second time is 1-2:5-10:5-10; in the step 1.7, the molar ratio of compound 6, compound 3 and Pd(dppf)Cl2·CH2Cl2 is 1-2:2-4:0.1-0.2; in the step 1.8, the molar ratio of compound BTDSCO, ammonium chloride and zinc powder is 1-2:6-10:10-15.
5. The method for preparing the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material according to claim 1, characterized in that: In the step 2, specifically: BTDSCN and TiO2 nanosheets were added to methanol, stirred for 30 minutes, ultrasonicated for 30 minutes to make them evenly dispersed, the methanol was rotary evaporated, and distilled water was added for hydrothermal reaction. After the reaction, the mixture was cooled, centrifuged, washed with deionized water for 4-5 times, and vacuum dried to obtain a BTDSCN / TiO2 nanosheet heterojunction composite material, which is a benzothiadiazole-titanium dioxide nanosheet heterojunction composite material.
6. The method for preparing the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material according to claim 5, characterized in that: The molar ratio of BTDSCN to TiO2 nanosheets is 0.05-0.1:1-2; the hydrothermal reaction temperature is 120-130°C, and the hydrothermal reaction time is 12-14h.
7. The method for preparing the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material according to claim 5, characterized in that: The preparation process of TiO2 nanosheets is as follows: Tetrabutyl titanate was added to the HF solution, stirred for 30 minutes, and then transferred to a stainless steel high-pressure reactor, and reacted at 180-190°C for 24-36 hours. After the reaction was completed, it was cooled, centrifuged, washed with deionized water 4-5 times, and vacuum dried to obtain TiO2 nanosheets.
8. Use of the benzothiadiazole-titanium dioxide nanosheet heterojunction composite material prepared by the method according to any one of claims 1 to 7 in photocatalytic degradation of organic pollutants.
Citation Information
Patent Citations
Benzothiadiazole functional dye molecule and preparation method thereof
CN116589457A